2020
DOI: 10.1111/pai.13385
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in farm children is more determined by genetic polymorphisms and in non‐farm children by environmental factors

Abstract: Background The asthma syndrome is influenced by hereditary and environmental factors. With the example of farm exposure, we study whether genetic and environmental factors interact for asthma. Methods Statistical learning approaches based on penalized regression and decision trees were used to predict asthma in the GABRIELA study with 850 cases (9% farm children) and 857 controls (14% farm children). Single‐nucleotide polymorphisms (SNPs) were selected from a genome‐wide dataset based on a literature search or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with the risk of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these risks.…”
Section: Discussionsupporting
confidence: 91%
“…Diverse microbial exposure in early life as well as the individual's personal capacity to mount adequate immunological responses seem to be crucial to avoid asthma and allergy development (28). A significant part of the genetic susceptibility for asthma and allergy may be driven by variation in genes contributing to immunological processes, depending also on differences in environmental exposure (28).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse microbial exposure in early life as well as the individual's personal capacity to mount adequate immunological responses seem to be crucial to avoid asthma and allergy development (28). A significant part of the genetic susceptibility for asthma and allergy may be driven by variation in genes contributing to immunological processes, depending also on differences in environmental exposure (28). While recent studies on the subject have used genome-wide association study (GWAS) data, crucial regions of the genome are not covered in this approach: the genetic locus containing multiple defensin genes including hBD-2 on chromosome 8 is one of them.…”
Section: Introductionmentioning
confidence: 99%